Optimal integration of solar energy in a district heating network. (March 2015) - Carpaneto, E.; Lazzeroni, P.; Repetto, M.
Abstract: The implementation of European Directive 2012/27 calls for the presence of a renewable share inside efficient district heating and cooling. Solar thermal energy can be a viable contribution to this aim but particular attention must be put into its integration inside the district heating systems. In fact, the variable and non-controllable nature of renewable heating must be handled by fulfilling users demand and coordinating its output with other controllable sources. Thermal energy storage is often necessary for exploiting the renewable sources at their best. An optimisation procedure has been developed to find the dispatching strategy for the different power sources present in the network. The optimisation procedure can be used at the planning level to find out the best sizing proportions of solar and conventional sources and for defining the optimal capacity of storage. After a brief description of the optimisation procedure and of its simulation modules, one test case is presented and results about advantages due to solar heating are discussed. Highlights: Model of the district heating systems with solar heating and thermal storage. Model of solar production in accordance with EN12975. Minimum cost optimisation on a week scheduling with electricity market price. Study case in Northern Italy.